Implementasi Model Pembelajaran Kooperatif Dalam Meningkatkan Mutu Pembelajaran Tematik Kelas Awal Di Sekolah Dasar - Daningsih Kurniasari; Helmia Tasti Adri (Pedir Research Institute, 2022)
This research aims to describe the development of thematic quality learning elementary school at 1st – 3rd grade through cooperative learning model. The purpose of thematic learning is to make students easier to focus on one theme because the material is provided through the clear theme. Further, the students can learn and improve every basic of competencies in one theme. This purpose is often not achieved because of teachers’ implementation learning method for teaching which is not interesting for students. Hence, it can cause the low quality of thematic learning. Hence, the teachers’ learning innovations is needed by applying a more stimulating learning model in order to make students learn more cooperative. It can be applied in using cooperative learning. This research used survey method through interview and observation on 1st – 3rd teacher in elementary school. The result of study is showed that the thematic learning in 1st – 3rd grade can be increased through implementation cooperative learning.